THE RESPONSIBILITY OF THE STATE ON TRANSBOUNDARY HAZE POLLUTION AFTER THE RATIFICATION OF AATHP: CASE OF INDONESIA - Muhammad Arizka Wahyu (FH IPOLS 15 UMY 109, 2015)
*109 Land and forest fires in Indonesia has resulted the economic and ecological losses caused by opening the land (land clearing) with burning land. Land and forest fires in Sumatra and Kalimantan is now not only a national issue, but also became an international issue because it arises the transboundary haze pollution. Beside the loss in Indonesia itself, the smoke also disrupt neighboring countries, such as Malaysia, Brunei and Singapore. Every year Malaysia and Singapore as countries affected by transboundary haze pollution filed a strong protest to the Indonesian government. Based on the principle of international law of state responsibility, Indonesia should be responsible for the transboundary haze pollution. Because of it has disrupted the environment of other countries. On June 10, 2002, ASEAN countries agreed to sign the 1997 ASEAN Agreement on Transboundary Haze Pollution (AATHP) to address land and forest fires in Southeast Asia and AATHP entered into force on 25 November 2003. Then, in 2014, Indonesia became the last country to ratify AATHP. The type of this research is a normative legal research. By using a qualitative descriptive method, the research aims to describe the responsibility of Indonesian government on transboundary haze pollution based on international law of state responsibility and ASEAN Agreement on Transboundary Haze Pollution (AATHP) and also the regulations and conventions especially that related to the transboundary haze pollution. The result shows that based on international law of state responsibility, Indonesian government should be responsible for the transboundary haze pollution and after ratification the ASEAN Agreement on Transboundary Haze Pollution, Indonesia as the pollutant country cannot be required to pay compensation fully because it was a shared responsibility of the ASEAN countries.